2019
DOI: 10.2147/cia.s223048
|View full text |Cite
|
Sign up to set email alerts
|

<p>Risk Factors For Hyperuricemia In Chinese Centenarians And Near-Centenarians</p>

Abstract: Hyperuricemia is an important potential pathogenic factor for hypertension, cardiovascular disease and stroke. The current study aimed to investigate the prevalence of hyperuricemia and its relationship to lifestyle characteristics and dietary habits in centenarians and near-centenarians. Patients and methods: In total, 966 centenarians and 788 near-centenarians were included. Community-based surveys were conducted to collect information about lifestyle. Blood examinations were performed using enzymatic assays… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 28 publications
(34 reference statements)
2
26
0
Order By: Relevance
“…Meanwhile, in the DII calculation, there was no differentiation between plant-sourced proteins and animal-sourced proteins. A higher intake of protein and fat may also suggest a higher intake of animal food, which is thought to be associated with hyperuricemia [30]. We also found that alcohol intake in the hyperuricemia group was higher than the nonhyperuricemia group, which was consistent with other studies.…”
Section: Discussionsupporting
confidence: 92%
“…Meanwhile, in the DII calculation, there was no differentiation between plant-sourced proteins and animal-sourced proteins. A higher intake of protein and fat may also suggest a higher intake of animal food, which is thought to be associated with hyperuricemia [30]. We also found that alcohol intake in the hyperuricemia group was higher than the nonhyperuricemia group, which was consistent with other studies.…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, measuring anthropometric indices such as body mass index (BMI), neck circumference (NC), waist circumference (WC) and hip circumference (HC) using tape or a scale is relatively easy (11). It has been confirmed that BMI (12)(13)(14), waist circumference (15)(16)(17) and hip circumference are positively correlated with the risk of hyperuricemia in different populations. However, it is not always feasible and accurate to measure WC, HC and BMI in the winter with heavy clothes or postprandially.…”
Section: Introductionmentioning
confidence: 99%
“…An effective strategy is urgently needed to decrease the levels of serum urate for patients with hyperuricemia. Dietary factors and lifestyle were attached to an important concern in related studies owing to the characteristics of changeability (11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%